Effect of oxidative stress on tumor suppressor protein p53 and some biochemical markers in breast cancer patients in Erbil governorate - Ashtee A. Ahmad; Kamaran Abdoulrahman (Zanco Journal of Pure and Applied Sciences, 2020)
The present study was conducted to observe the effect and association of oxidative stress on breast cancer, as well as evaluate the alteration of the serum lipid profile, hepatic and kidney biomarkers and serum tumor suppressor protein p53 in breast cancer patients in female as an important objective and determine the relationship between serum p53 with nitric oxide NO, malondialdehyde MDA, superoxide dismutase SOD, lipid profile, liver and kidney functions. In this study 80 subjects were conducted 50 women who had breast cancer as a patient group, and 30 healthy women were conducted as a control group. Blood samples were taken from both patients and control group, who were aged between (18-75) years old. The results of this study revealed that the median levels of serum NO, creatinine and the mean level of serum HDL are significantly lower in patients group with breast cancer than those in control group. Whereas, the median levels of serum MDA, TG, LDL, ALT, AST, and the mean level of serum CH are significantly higher in patients group with breast cancer rather than in control group. While, there are negative weak significant correlations between p53 with MDA, CH, TG and ALT. ROC curve analysis exhibit that serum NO, MDA, TG, HDL, ALT and AST are excellent biomarkers for the diagnostic accuracy of breast cancer in female as a result of the high level of AUC. Whereas, this study demonstrates that serum p53 is not a good biomarker for female breast cancer with AUC value 0.5636. Although, it is known that serum p53 is a tumor suppressor protein that plays a crucial role in the inhibition of cancer development. In conclusion, the results revealed that patients with breast cancer have a systemic oxidative stress rising due to human tumor cells produce large quantity of ROS, which plays a crucial role in liver diseases, abnormality of renal function and hyperlipidemia. Most possibly due to the endothelial dysfunction which consequently is risk factor for patient’s health.